2021
DOI: 10.3390/mi12091111
|View full text |Cite
|
Sign up to set email alerts
|

Poly (Ethylene Glycol) Methyl Ether Methacrylate-Based Hydrogel and Cerium(IV) Oxide Nanoparticles as Ophthalmic Lens Material

Abstract: The functional hydrogel lens containing 2-hydroxyethylmethacrylate (HEMA) was manufactured by thermal polymerization. The physical properties of the produced hydrogel lens were measured and analyzed. In this study, HEMA, ethylene glycol dimethacrylate (EGDMA), and azobisisobutyronitrile (AIBN) were used for thermal copolymerization. Additionally, poly (ethylene glycol) methyl ether methacrylate (PEGMEMA), 3-(Triethoxysilyl) propyl isocyanate (TEPI), and cerium(Ⅳ) oxide nanoparticles were used as additives to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In particular, micelles constructed of amphiphilic block polymers such as PEGMA have been widely studied in drug administration with the goal of tumor‐targeted theranostics. [ 23–35 ] Polymeric nanocomposites containing zinc oxide can help prepare biocompatible nanoparticles and effectively deliver chemotherapy drugs to cancer cells. Many studies have shown that Zinc oxide nanoparticles can be used to provide chemotherapy agents as a cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, micelles constructed of amphiphilic block polymers such as PEGMA have been widely studied in drug administration with the goal of tumor‐targeted theranostics. [ 23–35 ] Polymeric nanocomposites containing zinc oxide can help prepare biocompatible nanoparticles and effectively deliver chemotherapy drugs to cancer cells. Many studies have shown that Zinc oxide nanoparticles can be used to provide chemotherapy agents as a cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, micelles constructed of amphiphilic block polymers such as PEGMA have been widely studied in drug administration with the goal of tumor-targeted theranostics. [23][24][25][26][27][28][29][30][31][32][33][34][35] Polymeric nanocomposites containing zinc oxide can help prepare biocompatible nanoparticles and effectively deliver chemotherapy drugs to cancer cells.…”
mentioning
confidence: 99%
“…Contact lenses, originally used for vision correction, recently have been adopted for ocular delivery of antimicrobial agents to treat infectious keratitis due to extended corneal contact, drug retention time in ocular surface, improved corneal permeation, and biosafety. , In particular, various drug delivery strategies have been extensively applied in contact lenses (CLs), including soaking, molecular imprinting, embedding, and surface coating. For example, Liu et al prepared a multilayer-silver nanoparticle (AgNP)-loaded contact lens through a mussel-inspired facile method for early treatment of bacterial keratitis . However, poor biosafety and biocompatibility caused by the release of metal ions may restrict their applications .…”
Section: Introductionmentioning
confidence: 99%